Nonlinear mechanics of bioinspired tensegrity systems - Mendes, Alex Neves Brandão (2021)
Tensegrity comes from the concept that the structure relies in the interaction between tension and compression, opposing forces to maintain the structure integrity. Essentially, tensegrity structures are composed by bars (struts) and strings (cables), where the bars work under compression whereas the strings work under tension. Biological systems present several characteristics of tensegrity structures such as the legs of animals where the bars represent the bones and the strings represent the tendons or ligaments. This work deals with the nonlinear mechanics of bioinspired tensegrity structures. A formulation considering the force density matrix approach is used to model the equilibrium equations of the structure based on node mapping. Lagrange multipliers are employed to represent constraints related to ground interaction. Equilibrium configurations are defined from an optimization procedure employing the LevenbergMarquardt method. A minimal regular tensegrity prism is investigated. The model is verified establishing comparisons among analytical results, experimental data and numerical simulations. The softening and hardening behaviors are investigated in order to highlight the tensegrity properties. An investigation of the tensegrity capability to represent a human foot is carried out, analyzing three main aspects: weight distribution, geometry and physiology. Shape memory alloy (SMA) is employed to provide foot actuation and its thermomechanical behavior is described by considering a polynomial constitutive model. The tensegrity prosthesis performance is compared with high performance prosthesis, showing that it is an interesting alternative with respect to mechanical resistance. Regarding physiology, the foot movements are mimicked from SMA actuation through electric current.Também disponível online.